Witnessing Intimate Partner Violence as a Child and Associated Consequences. Issue 21 (November 2022) - Stiller, Anja; Neubert, Carolin; Krieg, Yvonne
Intimate partner violence (IPV) continues to be a global problem. The increasing international research, focussing on children who witness IPV between their parents, indicates that these circumstances might influence children in different ways. Despite these efforts, little evidence stems from Germany. Using data from a German school student survey from 2017 and 2019 ( N = 21, 382), this paper aims to examine the consequences of witnessing IPV. The present paper takes a closer look at children's violent behaviour, attitudes and quality of life while controlling for other potential influences (e.g. physical and psychological child abuse). Results indicate that IPV has a significant negative effect on children's quality of life, in particular on children's sense of security at home and children's life satisfaction. No other effects were significant. In discussing these complex dynamics, the results of the present study highlight the importance of considering children who witness IPV as direct victims. A home with personal threats cannot provide emotional and physical security. Coping with this absence of a secure base at home may lead to the neglect of important developmental tasks during that time, which can have possible far-reaching implications on different areas of children's lives (e.g. social competence). Further research examining the severity and duration of witnessing IPV within the context of a longitudinal design is recommended.